Molecular studies of the salivary glands of the pea aphid, Acyrthosiphon pisum (Harris) - Mutti, Navdeep S. (Kansas State University, 2006)
Salivary secretions are a key component of aphid-plant interactions. Aphids’ salivary proteins interact with plant tissues, gaining access to phloem sap and eliciting responses which may benefit the insect. In an effort to isolate and identify key components in salivary secretions, we created a salivary gland cDNA library. Several thousand randomly selected cDNA clones were sequenced. We grouped these sequences into 1769 sets of essentially identical sequences, or clusters. About 22% of the clusters matched clearly to (non-aphid) proteins of known function. Among our cDNAs, we have identified putative oxido-reductases and hydrolases that may be involved in the insect's attack on plant tissue. C002 represents an abundant transcript among the genes expressed in the salivary glands. This cDNA encodes a novel protein that fails to match to proteins outside of aphids and is of unknown function. In situ hybridization and immunohistochemistry localized C002 in the same sub-set of cells within the principal salivary gland. C002 protein was detected in fava beans that were exposed to aphids, verifying that C002 protein is a secreted protein. Injection of siC002-RNA caused depletion of C002 transcript levels dramatically over a 3 day period after injection. With a lag of 1 – 2 days, the siC002-RNA injected insects died, on average 8 days before the death of control insects injected with siRNA for green fluorescent protein. It appears, therefore, that siRNA injections of adults will be a useful tool in studying the roles of individual transcripts in aphid salivary glands.
Keywords: Salivary Ggands; Pea aphid; RNAi; Biology, Entomology (0353); Biology, Molecular (0307)